From indole to pyrrole, furan, thiophene and pyridine: Search for novel small molecule inhibitors of bacterial transcription initiation complex formation. Issue 6 (15th March 2016) - Thach, Oscar; Mielczarek, Marcin; Ma, Cong; Kutty, Samuel K.; Yang, Xiao; Black, David StC.; Griffith, Renate; Lewis, Peter J.; Kumar, Naresh
Graphical abstract: Abstract: The search for small molecules capable of inhibiting transcription initiation in bacteria has resulted in the synthesis of N, N ′-disubstituted hydrazines and imine-carbohydrazides comprised of indole, pyridine, pyrrole, furan and thiophene using the respective trichloroacetyl derivatives, carbohydrazides and aldehydes. Replacement of the indole moiety by smaller heterocycles linked by CONHNC linkers afforded a broad variety of compounds efficiently targeting the RNA polymerase– σ 70 / σ A interaction as determined by ELISA and exhibiting increased inhibition of the growth of Escherichia coli compared to Bacillus subtilis in culture. The structural features of the synthesized transcription initiation inhibitors needed for antibacterial activity were identified employing molecular modelling and structure–activity relationship (SAR) studies.